Synthesis, Characterization, and Catalytic Activity of Pd(II) Salen-Functionalized Mesoporous Silica - Rotcharin Sawisai; Ratchaneekorn Wanchanthuek; Widchaya Radchatawedchakoon; Uthai Sakee (Journal of Chemistry)
Salen ligand synthesized from 2-hydroxybenzaldehyde and 2-hydroxy-1-naphthaldehyde was used as a palladium chelating ligand for the immobilization of the catalytic site. Mesoporous silica supported palladium catalysts were prepared by immobilizing Pd(OAc)2 onto a mesoporous silica gel through the coordination of the imine-functionalized mesoporous silica gel. The prepared catalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), inductivity couple plasma (ICP), nitrogen adsorption-desorption, and Fourier transform infrared (FT-IR) spectroscopy. The solid catalysts showed higher activity for the hydroamination of C-(tetra-O-acetyl-β-D-galactopyranosyl)allene with aromatic amines compared with the corresponding homogenous catalyst. The heterogeneous catalytic system can be easily recovered by simple filtration and reused for up to five cycles with no significant loss of catalytic activity.